2019
DOI: 10.1017/s1355617719001334
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychological Alterations in Narcolepsy with Cataplexy and the Expression of Cognitive Deficits

Abstract: Objectives:The objective of our study was to assess attention processes and executive function in patients with narcolepsy with cataplexy (NT1). To do so, we compared the results with those of a control group from the general population using an extensive neuropsychological test battery.Methods:We studied 28 patients with NT1 and 28 healthy control participants matched for age, gender, and educational level. They all completed questionnaires on sleepiness, anxiety, and depression symptoms. In addition, they un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 48 publications
0
10
0
1
Order By: Relevance
“…Park and Moraes showed that NT1 patients need more time than controls to complete both parts of the TMT [32,34]. The latter also reported a greater time cost of attentional shift in NT1 compared to controls, while this difference was not observed in the study of Medrano-Martinez [29]. Delazer and Zamarian administered the intra/extra dimensional set-shift test and did not find differences between NT1 and controls in the number of completed stages, trials needed to complete a stage, errors and errors adjusted for number of stages [17,18].…”
Section: Set-shiftingmentioning
confidence: 91%
See 3 more Smart Citations
“…Park and Moraes showed that NT1 patients need more time than controls to complete both parts of the TMT [32,34]. The latter also reported a greater time cost of attentional shift in NT1 compared to controls, while this difference was not observed in the study of Medrano-Martinez [29]. Delazer and Zamarian administered the intra/extra dimensional set-shift test and did not find differences between NT1 and controls in the number of completed stages, trials needed to complete a stage, errors and errors adjusted for number of stages [17,18].…”
Section: Set-shiftingmentioning
confidence: 91%
“…Park and Yoon administered the Stroop and reported no differences between NT1 and controls in terms of correct responses and RTs to correct responses [30,34]. Similarly, Kim and Medrano-Martinez did not find any differences between NT1 and controls at the Stroop word and colour test [29,31]. Moraes administered the Victoria Stroop without showing differences in accuracy between NT1 and controls but patients displayed slower RTs than controls [32].…”
Section: Inhibitionmentioning
confidence: 93%
See 2 more Smart Citations
“…Os transtornos de humor têm por principal característica a alteração no humor ou no afeto, comportamento, jeito de sentir e pensar, ou seja, afetam as funções cognitivas, prejudicando a atenção, a velocidade de processamento de informação, a fluência verbal e a resistência na interferência à estímulos. São considerados agravos à saúde mental nos quais as alterações de humor e afeto e podem se prolongar entre períodos de depressão e exaltação excessiva ou de euforia, ou ambos (American Psychiatric Association, 2014;Medrano-Martinez et al, 2018). As causas e os efeitos dos transtornos de humor devem ser entendidos, levando em consideração as dimensões biológicas, psicológicas e sociais dos indivíduos.…”
Section: Introductionunclassified